A study on Rural-Urban Purchase Motivators for Air Conditioners in Punjab : Implications for Marketers - Thakur, Anand (Journal of Contemporary Research in Management (JCRM), 2013)
Indian rural market is emerging stronger with a gradual increase in disposable income of the rural folk. The structure of the Indian economy indicates that a significant portion of the total income is derived from agriculture income. In addition, better procurement prices fixed for various crops and better yields due to many research programmes have also contributed to the strengthening of the rural markets. ‘Go rural’ is the slogan of marketers after analyzing the socio-economic changes in villages. The Rural consumers have become the prime target market for consumer durable and non-durable products, food, construction, electrical, electronics, automobiles, banks, insurance companies and other sector. The Present study explores the significant motivators for Air-conditioner purchase in economically significant rural and urban areas of Prosperous State of Punjab. A survey of 596 rural & urban respondents (with use of Z test) brings out significant findings regarding ACs purchase. Finally, some useful implications for marketers have been offered at the end.